Antimicrobial and Anthelmintic Activity of Pyrazolin-5-one Derivatives - Om Prakash, E.; Sree Devi, E.; Rao, J.T. (Asian Journal of Chemistry, 2010)
Some new 1-(2',4'-dinitro phenyl), 3-methyl, 4-(aryl hydrazono)- 2-pytazolin-5-one were pepared by reacting with different ethyl 2-aryl hydrazono-3-oxybutytate derivatives- with 2,4-DNP. The products were screened for their antimicrobial and anthelmintic activities.